A single-ion conducting quasi-solid polymer electrolyte made from synthetic rubber for lithium metal batteries - Kun-Ling Liu; Chung-Hsiang Chao; Hsin-Chieh Lee; Cheng-Hung Liao; Jason Fang; Nae-Lih Wu; Chi-Yang Chao (Electrochemistry Communications, 2023)
A lithium-ion conducting triblock copolymer bearing pendant lithium sulfonates, termed as SSEBS-Li, is derived from commercial synthetic rubber poly(styrene-block-(ethylene-ran-butylene)-block-styrene); and free-standing quasi-solid polymer electrolyte (QSPE) membranes made of demonstrate high efficiency and high safety in the application for lithium metal batteries (LMBs). SSEBS-Li possesses a hybrid molecular structure containing “soft” segments that enable seamless contact with the lithium metal; and “hard” segments possessing anchored anions that offer continuous pathways to benefit lithium ion conduction and homogeneous lithium deposition. The unique molecular architecture features the QSPE membranes interpenetrated network microstructures to provide good mechanical strengths and ductility at a thickness of 25 µm. A high lithium ion conductivity of up to 5 × 10-4 S cm−1 at ∼ 35 wt% liquid electrolyte uptake is achieved, along with a high lithium transference number of 0.92 at room temperature. Galvanostatic cycling studies prove the excellent capability of SSEBS-Li QSPE in suppressing lithium dendrite growth. The Li//QSPE//LFP cell exhibits a high discharge capacity and excellent long-term stability after 300 cycles at 0.5C and room temperature without deleterious decay, elucidating a feasible and economical approach to improve the stability and safety of LMBs.